De laatste oude huizen van Rotterdam. Haringvliet Zz (Bulletin KNOB, 2004)
The approximately ten houses preserved along the Haringvliet after 1940, provide an insight into the development of Rotterdam merchant houses. This unique type of house was built because of local conditions. As a result of the soft building land and high flood tides the warehouse was downstairs and the living space upstairs in these houses. Thus the weight of the goods was divided over the floors and the walls were less burdened. The joint walls prescribed here made complete rebuilding of the houses almost impossible. Their history consisted in minor and major conversions. Because the street was raised by a total of nearly two metres, the inner height of the warehouses was diminished, so that the facades had to be renovated several times.Around 1675 the first floor of these expensive houses became a favourite project. This floor could only be constructed above the warehouse and covered the entire depth of the house. A frequently used lay-out was developed, with a light well in the middle and two large rooms both in the front and the back part of the house. On each of the exterior walls there was a hall, and on both sides of the light well a large room. In both parts of the house there were staircases, of which the one in the back part was most important. In the light well there was a low connecting room deriving its name from the crowning lantern.On one side there was a hallway with stucco vaults, in many cases extending up to the façade, from where the light flowed in. This hallway was connected to the front door by a monumental, little-used staircase. The domestic rooms were accommodated in the back part under the first floor. The entrance to these rooms was through the warehouse.Gradually the household began to require more space, just as the merchant's administration. Around 1700 the warehouse was abandoned in the larger houses and replaced by a room on the street side with one or two windows next to the monumental front door. Only one entrance was left in these large houses, which was used by everyone alike. Consequently, along the harbours two types of houses were to be found, the traditional one with a warehouse downstairs and the more modern type with a domestic ground floor.A design for a contest dating from 1860 proposes a similar house, on a site that is strongly reminiscent of the house along the Haringvliet. It is the final stage in the development that took place along the Haringvliet. The houses built in the new districts a few years later, were smaller and more practical. The new functions. such as office space and household facilities could no longer be accommodated within the walls of the houses.